POLA INTERAKSI BELAJAR MENGAJAR Kajian Tafsir Tarbawi : Surat Abasa Ayat 1-10 - Abdul Muis, Cecep (HASBUNA : Jurnal Pendidikan Islam, 2024)
Interaction in the teaching and learning process is a very determining factor in achieving learning objectives. Principles in teaching and learning Accompanied by appropriate learning materials and the methods used, influence the achievement of teaching and learning objectives because if interactions in learning are not harmonious, then the learning objectives will not be achieved. In writing this thesis, the author used qualitative research using library research methods. This library research involves reading, reviewing, describing and analyzing literature from various sources of tafsir books and appropriate educational books. The focus in writing this thesis is the study of the interpretation of Surah Abasa verses 1-10. The method used in this research is a qualitative descriptive method. This type of research is library research, namely research whose main object is books or other library sources. This means that data is searched for and found through literature review of books that are relevant to the discussion. Primary data in this research was taken from Surah Abasa verses 1-10, Tafsir Al-Misbah Surah Abasa verses 1-10 and secondary data from books that have relevance to strengthen arguments and complete the results of this research were taken from notes such as journals, papers, the internet and relevant materials that can be taken as sources. In this research, the researcher acts as the main instrument. Data identification is assisted by using explanations from several relevant interpretation books and other supporting books. The data collection technique in this research uses documentation study or literature study techniques. The analysis technique for this writing is content analysis, which is a technique used to draw conclusions through efforts to find message characteristics and is carried out objectively and systematically. Based on the results of research conducted by the author regarding teaching and learning interactions in the Al-Qur'an, Surah Abasa verses 1-10, namely: The pattern of teaching and learning interactions contained in Surah Abasa verses 1-10 is a three-way interaction pattern, the principles of learning include: Mujahadah, istiqomah, and iffah. Teaching principles include: Ask questions when prepared by the teacher, do not provoke the teacher's anger, be persistent in learning, do not order the teacher too much. Teaching ethics include: not discriminating, always being patient, being kind, and reprimanding gently.